Enhancing physical attributes and performance in badminton players: efficacy of backward walking training on treadmill - Omkar Sudam Ghorpade; Moattar Raza Rizvi; Ankita Sharma; Harun J. Almutairi; Fuzail Ahmad; Shahnaz Hasan; Abdul Rahim Shaik; Mohamed K. Seyam; Shadab Uddin; Saravanakumar Nanjan; Amir Iqbal; Ahmad H. Alghadir (BMC, 2024)
Abstract Background Badminton, a dynamic sport, demands players to display exceptional physical attributes such as agility, core stability, and reaction time. Backward walking training on a treadmill has garnered attention for its potential to enhance physical attributes and optimize performance in athletes while minimizing the risk of injuries. Objective By investigating the efficacy of this novel approach, we aim to provide valuable insights to optimize training regimens and contribute to the advancement of sports science in badminton. Methodology Sixty-four participants were randomized into a control group (n = 32) and an experimental group (n = 32). The control group received routine exercise training, while the experimental group received routine exercise training along with additional backward walking training on the treadmill. Pre- and post-intervention measurements were taken for core stability using the Plank test, balance using the Star Excursion Balance test, reaction time using the 6-point footwork test, and agility using the Illinois Agility test. Results The results showed that the experimental group demonstrated significant improvements in core stability (p < 0.001), balance (p < 0.001), reaction time (p < 0.05), and agility (p < 0.001) compared to the control group. The backward walking training proved to be effective in enhancing these physical attributes in badminton players. Conclusion Incorporating backward walking exercises into the training regimen of badminton players may contribute to their overall performance.